Sistem Otomasi Suhu dan Kelembaban Pada Greenhouse Berbasis Sensor DHT22 dan Mikrokontroler - Irwan Heryanto/Eryk; Swasmitha Arum Kusuma; Mohammad Noor Hidayat (Politeknik Negeri Malang, 2025)
Automatic control of temperature and humidity in greenhouses remains a critical challenge in precision agriculture, particularly in areas with limited access to modern technologies. This study aimed to design and implement an automated environmental control system using the DHT22 sensor and an Arduino microcontroller. The system was programmed to activate actuators, namely a water pump and a buzzer, based on predefined temperature and humidity thresholds. The research employed a hardware-based experimental method that included system programming, piping layout for water distribution, and field testing to validate sensor accuracy and control logic performance. The experimental results showed that the DHT22 sensor achieved high accuracy, with a temperature error of 0.02% and humidity errors ranging from 0.00% to 0.16%. The control logic functioned as expected, activating actuators only when the setpoint conditions were met, and the water distribution system operated efficiently using a 210-watt pump. Compared to prior studies that primarily focused on monitoring or single-aspect automation, this research offered a more comprehensive approach by integrating control logic, mechanical design, and electrical efficiency. The findings supported and expanded on previous work, particularly those utilizing similar sensors, but added value through direct implementation and real-world testing. This study contributed a practical and replicable solution for small- to medium-scale greenhouse automation, offering a low-cost and energy-efficient alternative for climate regulation in controlled agricultural environments